Selected views on human nature and their implications on education - Abdul Razak, Mohd Abbas; Haneef, Sayed Sikandar Shah; Mustapha, Maziah (Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Indonesia, 2018)
Even though the evolution of time and scientific knowledge have provided humanity with the latest understanding on the concept of man, nevertheless man is too complicated to be comprehended in his entirety through any single study carried out on him. As for this reason, the study on man has become perennial in nature. Human nature as a topic more popularly discussed in psychology has caught the attention of many concerned parties from other fields of research. Perhaps some of the most interested people in the study of man will be theologians, philosophers, sociologists, psychologists, anthropologists, biologists, etc. It is highly improbable for parents, psychologists, counselors and teachers to render their best help and services to their subjects without having the proper understanding on the concept of man. Due to this fact, this qualitative study was conducted to analyze some selected views on human nature. Ideas provided by psychoanalysis, radical behaviorism, humanistic and Islamic psychologies were analyzed. Upon analyzing the different concepts on human nature, the researchers examined the implications and possible outcomes when such concepts are applied in the field of education. The researchers employed the textual-analysis method in interpreting the pertinent data related to this study.